Kajian pemboleh-pemboleh ubah yang mempengaruhi aras pengetahuan, tindakan dan kesedaran murid sekolah rendah di Johor terhadap isu alam sekitar - Liew Abdullah, Nurul Hidayah (2015)
The main issue in this research is about primary school pupils’ environmental awareness which has yet to achieve the prescribed objectives despite the implementation of cross curriculum environmental education which has been implemented in 1988. This research was carried out to (i) identify teachers’ views about the effectiveness of the year 6 science curriculum in terms of pupils’ awareness on the environment; (ii) study the knowledge, perceptions, attitudes and behavior between urban and rural primary school pupils on environmental issues; (iii) review the constraints that exist in preserving the environmental awareness among pupils and (iv) develop a model to increase pupils’ awareness on the environment. The research area for this research was the administration unit of Kulaijaya District Education Office. There were 685 pupil respondents involved in this research (questionnaire), 81 pupil respondents (interview), 58 administrator respondents and 225 parent respondents who were selected randomly. For 22 teacher respondents they were selected based on purposive sampling. Quantitative and qualitative methods were used in this research to obtain a more robust research result. Researched data were analyzed using descriptive statistics for variable descriptions and inferential statistical t-test, Person correlation, Spearman’s rho, multiple regression and partial least square (PLS) and Structural Equation Modeling (SEM). As for qualitative data, they were analyzed manually. Research findings showed that year 6 Science curriculum was not appropriate and needed improvement to meet the current demands. Analyses of data on the knowledge, perception, attitudes, and behavior showed no significant difference between school’s locations with each producing t=1.005 (p≤.315); t=-1487 (p≤.137); t=-.687 (p≤.492) and t=1.413 (p≤.158). The data also showed that all constructs were related to each other and all r values were at significant level of p≤0.01. The main constraints faced by the implementers in school were the lack of funding, material, time, knowledge and monitoring by top management. The environmental awareness model was constructed based on results of this research, aimed at increasing the awareness of pupils on the environment. SEM test showed that the model is coherent with the observed data. This shows that this model is acceptable. In conclusion, the cooperation between all stakeholders is significant in ensuring the enhancement of pupils’ environment awareness.